Estimating the effect of Hungarian monetary policy within a structural VAR framework - Balázs Vonnák (Magyar Nemzeti Bank, 2005)
A standard approach in measuring the effect of monetary policy on output and prices is to estimate a VAR model, characterise somehow the monetary policy shock and then plot impulse responses. In this paper I attempt to do this exercise with Hungarian data. I compare two identification approaches. One of them involves the `sign restrictions on impulse responses' strategy applied recently by several authors. I also propose another approach, namely, imposing restrictions on implied shock history. My argument is that in certain cases, especially in the case of the Hungarian economy, the latter identification scheme may be more credible. In order to obtain robust results I use two datasets. To tackle possible structural breaks I make alternative estimates on a shorter sample as well. The main conclusions are the followings: (1) although the two identification approaches produced very similar results, imposing restrictions on history may help to dampen counterintuitive reaction of prices; (2) after 1995 a typical unanticipated monetary policy contraction (a roughly 25 basis points rate hike) resulted in an immediate 1 per cent appreciation of the nominal exchange rate (3) followed by a 0.3% lower output and 0.1-0.15% lower consumer prices; (4) the impact on prices is slower than on output; it reaches its bottom 4-6 years after the shock, resembling the intuitive choreography of sticky-price models; (5) using additional observations prior to 1995 makes identification more difficult indicating the presence of a marked structural break.
Keywords: C11; C32; E52; 330; structural VAR; monetary transmission mechanism; identification; sign restriction; monetary policy shocks; Geldpolitik; Schock; Wirkungsanalyse; Geldpolitische Transmission; VAR-Modell; Schätzung; Ungarn